Improving segments rigidity during sports movements - Benouaich L.; Natta F.; Thoreux P.; Rouch P. (13th International Symposium on the 3D Analysis of Human Movement, 14-17 July, 2014, Lausanne, Switzerland, 2014)
Soft tissue artifacts remain one of the major limits in video-based motion analysis. The benefits of using rigid markers clusters instead of skin-fixed markers to determine the segments frames during human movement never reached consensus. The aim of that study is to evaluate the dislocation artifact at ankle, knee and hip joint with the cluster method and to quantify the deformation artifact of tibia and femur with the skin-fixed markers and with a mean cluster based method during five standardized movements: gait, fast running, half-squat, low counter-movement jump and kicks. Preliminary results showed that the mean cluster based method could provide more rigid segments than the classical skin-fixed markers method, in particular for movements involving high knee range of motion or impacts. Then, with the easier solving of marker loss and the improved comfort, this clusterbased method could be a better solution to study kinematics of sports movements.